Apoptotic response through a high mobility box 1 protein-dependent mechanism in LPS/GalN-induced mouse liver failure and glycyrrhizin-mediated inhibition. - Noriyuki Kuroda; Kouji Inoue; Tadayuki Ikeda; Yaiko Hara; Kenjiro Wake; Tetsuji Sato (PLoS ONE, 2014)
HMGB1 is a nuclear component involved in nucleosome stabilization and transcription regulation, but extracellularly it is able to serve as a potential late mediator of lethality. In the present study, we explored inflammation-promoting activity of HMGB1 and blockade of extracellular release of HMGB1 by glycyrrhizin (GL) in LPS/GalN-triggered mouse liver injury. At 1 to 10 h after LPS/GalN-treatment, mice were anesthetized to collect blood from heart puncture, and serum transaminase and HMGB1 were evaluated. Administration of LPS/GalN precipitated tissue injury associated with time-dependent alteration in HMGB1 serum levels. At 8 h nuclear immunoreactive products were remarkably reduced and extracellular HMGB1 expression was found exclusively in the pericentral foci. The treatment with GL significantly down-regulated the serum levels of ALT, AST, and HMGB1 in addition to the strong inhibition of tissue injury and extracellular immunoreactivity to HMGB1 and to acetylated-lysine. Furthermore, GL brought about a significant decrease in the number of apoptotic hepatocytes labeled with TUNEL-method. On the basis of these results, three apoptosis-associated genes were identified with microarray analysis and real-time PCR. The ChIP-assay revealed the binding of HMGB1 protein to Gsto1 promoter sequence in LPS/GalN-treated mice and the remarkable decrease in combined HMGB1 protein by GL. The current findings claim that a single injection of LPS/GalN might stimulate apoptosis of hepatocytes through the binding of HMGB1 protein to Gsto1 promoter region and that GL-treatment might prevent the apoptosis and inflammatory infiltrates caused with LPS/GalN-injection by disturbing the binding of HMGB1 protein to Gsto1 promoter sequence.